2016
DOI: 10.1016/j.jrp.2016.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Intelligence and Extraversion in the neural evaluation of delayed rewards

Abstract: Temporal discounting (TD), the preference for earlier, smaller rewards over delayed, larger rewards, is a pervasive phenomenon that covaries with Big Five personality traits and Intelligence (IQ). This study provides novel insight by identifying correlates for IQ and Extraversion in the neural representation of TD preferences. An intertemporal choice task was employed, where offers were sequentially presented, distinguishing between one evaluation phase (first offer is presented) and one comparison phase (seco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(14 citation statements)
references
References 63 publications
1
10
0
Order By: Relevance
“…Perhaps HD-tDCS over this brain region helped the participants gain a more appropriate time perspective, and consequently reducing their temporal discount. Indeed, previous studies have already shown that activity in left DLPFC was positively associated with a preference for delayed rewards ( McClure et al, 2007 ; Christakou et al, 2011 ; Civai et al, 2016 ) and lower delay discounting rates ( Hayashi et al, 2013 ; Sheffer et al, 2013 ). Although previous discussions about time perspective in decision making focused on future discounting, it also seems appropriate to consider time perspective when examining decision making based on past events (e.g., IGT).…”
Section: Discussionmentioning
confidence: 89%
“…Perhaps HD-tDCS over this brain region helped the participants gain a more appropriate time perspective, and consequently reducing their temporal discount. Indeed, previous studies have already shown that activity in left DLPFC was positively associated with a preference for delayed rewards ( McClure et al, 2007 ; Christakou et al, 2011 ; Civai et al, 2016 ) and lower delay discounting rates ( Hayashi et al, 2013 ; Sheffer et al, 2013 ). Although previous discussions about time perspective in decision making focused on future discounting, it also seems appropriate to consider time perspective when examining decision making based on past events (e.g., IGT).…”
Section: Discussionmentioning
confidence: 89%
“…The link between Extraversion and dopamine, demonstrated in a number of studies using pharmacological manipulations, is now one of the most robust findings in all of personality neuroscience (Chavanon, Depue, Luciana, Arbisi, Collins, & Leon, 1994;Mueller et al, 2014;Rammsayer, 1998;Rammsayer, Netter, & Vogel, 1993;Wacker, Chavanon, & Stemmler, 2006;Wacker et al, 2013;. Similarly, neuroimaging studies have provided compelling evidence that Extraversion is associated with structural and functional alterations throughout the mesolimbic reward system (Civai, Hawes, DeYoung, & Rustichini, 2016;Cremers et al, 2011;DeYoung et al, 2010;Grodin & White, 2015;Lewis et al, 2014). Depue and Collins's (1999) theory also provided some insight into the algorithmic processes represented by reward-related circuits.…”
Section: Let Theory Be Your Guide: How Detailed Explanations Of Bmentioning
confidence: 95%
“…Since Whiteside and Lynam (2001) based the original UPPS Scales in part on the Big Five, it has been investigated whether these major dimensions of personality are also related to temporal discounting. The strongest association appears to be between steeper discount rates and higher levels of extraversion (Daugherty and Brase, 2010;Mahalingam et al, 2014;Civai et al, 2016), perhaps due to higher susceptibility to (direct) rewards in extraverted individuals (Ostaszewski, 1996;Hirsh et al, 2010). Similar to impulsivity, however, this association is of small effect: In a study of N = 5,888 participants, Mahalingam et al (2014) found a correlation of r = 0.10.…”
Section: Personality Traitsmentioning
confidence: 97%
“…Agerelated cognitive decline may also play a moderating role here (Kable et al, 2019). Generally, studies point to a combination of several variables: For instance, since the relation between the Big Five and temporal discounting is significant but rather low (see Personality Traits section), it can be assumed to be of some relevance (Civai et al, 2016), but additional variables should be considered. tested the hypothesis of shared working memory mechanisms, as represented by working memory capacity, which is the ability to actively maintain goal-relevant mental representations (such as future rewards), while suppressing irrelevant or competing information (such as immediate rewards; Engle, 2002Engle, , 2018.…”
Section: Intelligencementioning
confidence: 99%